HUBUNGAN KETERAMPILAN DASAR MENGAJAR GURU DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS X SMA N 1 MERANGIN - Adhe Flouren Tina; fe; Yohanes (Matedukasia, 2023)
The aim of the research is for describe significant relationship between skills base teach teachers with results study mathematics student class X SMA N 1 Merangin. Type study is approach quantitative correlational. Population totaling 325 students, determination sample use Taro Yamane formula and selected as many as 76 students as sample. Technique taking sample is simple random sampling with method lottery. Technique data collection in the form of questionnaire shaped scale likert. Instruments used consists of 41 statement items skills base teaching mathematics teacher. Based on analysis, the data is normally distributed and linear pattern. Technique analysis of the data used on hypothesis for test correlation use formula product moment correlation is obtained rcount > rtable or 0.9521 > 0.227 and testing significance coefficient correlation researcher use formula-Z test is obtained Zcount > Ztable or 8.2433 > 0.9997, so can concluded that there is significant relationship between skills base teach teachers with results study mathematics student class X SMA N 1 Merangin year lessons 2022/2023. For state big small influence variable X against Y is determined with formula coefficient determination obtained 90.65% influenced by variable skills base teaching teachers towards variable results Study and 9.35% influenced by other factors